Gender Differences in COVID-19 Lockdown Impact on Mental Health of Undergraduate Students - Amerio, Andrea; Bertuccio, Paola; Santi, Francesca; Bianchi, Davide; Brambilla, Andrea; Morganti, Alessandro; Odone, Anna; Costanza, Alessandra; Signorelli, Carlo; Aguglia, Andrea; Serafini, Gianluca; Capolongo, Stefano; et al. (Frontiers in Psychiatry, 2022)
Background: Prolonged university closures and social distancing imposed measures due to COVID-19 pandemic obliged students to at-home learning with online lectures and educational programs promoting potential social isolation, loneliness, hopelessness and episodes of clinical decompensation. Methods: A web-based cross-sectional survey was carried out in a university institute in Milan, Northern Italy, to assess the COVID-19 lockdown impact on mental health of undergraduate students. We estimated odds ratios (OR) and the corresponding 95% confidence intervals (CI) through multiple logistic regression models. Results: On the 8177 students, 12.8% reported depressive symptoms, 25.6% anxiety, 8.7% insomnia, and 10.6% reported impulsive tracts, with higher proportions among females than males. Having a person to care at home, a poor housing quality and a worsening of the working performance were positively associated to mental health symptoms. A poor housing quality showed a stronger positive association with depressive symptoms and impulsivity among males than females, as well as a worsening the working performance and both depressive and anxiety symptoms. The absence of private space was positively associated to depression and anxiety, stronger among males than females. Conclusions: To our knowledge, this is the first multi-disciplinary consortium study, involving public mental health, environmental health and architectural design. Further studies are needed to confirm or refute our findings and consequent recommendations to implement well-being interventions in pandemic conditions.